Answer:
![x=3,-4(2)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/k6txusxry1lsgqkbskl5solqw7gkblf1f1.png)
Explanation:
Given the quadratic equation:
![5x^2+7x-66=0](https://img.qammunity.org/2023/formulas/mathematics/college/4nubrc9yy9apmah8c0v4abub7ddjw9q1dq.png)
We want to solve for x by factoring.
To factorize, follow the steps below.
Step 1: Multiply the coefficient of x² and the constant.
![5*-66](https://img.qammunity.org/2023/formulas/mathematics/college/4fzqv8wqrruyh2sww2n6azyxkmbdbzrjbn.png)
Step 2: Find two numbers that multiply to give (5 x -66), and add to give the coefficient of x, 7.
![\begin{gathered} 5*-3*22=-15*22 \\ 22-15=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ecnsdmijh7p56bx7sdq5j9nd4rpowpe0zi.png)
Step 3: Rewrite the middle term with those numbers.
![\begin{gathered} 5x^2+7x-66=0 \\ 5x^2+22x-15x-66=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b5d32xk8ne2zbr35s4k2beb8wsy4p51nsz.png)
Step 4: Factor the first two and last two terms separately. Ensure that the expression in the brackets is the same.
![\begin{gathered} x(5x+22)-3(5x+22)=0 \\ (x-3)(5x+22)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qwnuryfpjous2j4oov3ir5lsgvuqt82kdt.png)
Step 5: Solve for x
![\begin{gathered} x-3=0\text{ or }5x+22=0 \\ x=3\text{ or 5x=-22} \\ x=3\text{ or }x=-(22)/(5) \\ x=3\text{ or }x=-4(2)/(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hehrqt7fhshufzg17mxby6dgr82k4i48jv.png)
The value of x is 3 or -4 2/5.